Islam dan Budaya Jawa, Pertemuan yang Terus Berkelanjutan - Priyatna, Yana; Sukmaranti, Galuh (Oratio Directa (Prodi Ilmu Komunikasi), 2025)
The synthesis between Islam and Javanese culture is presented in a book by Mark R. Woodward, who conducts ethnographic research and studies the manuscripts written by court scholars in Java. Javanese Islam, as analyzed in Woodward’s book "Islam Jawa, Kasalehan Normatif Versus Kebatinan," is translated from "Islam in Java: Normative Piety and Mysticism." It portrays Islam as teaching normative piety and inner spirituality. Islam encompasses not only tauhid (the oneness of God) and fiqh (law) but also teaches tasawuf (Sufism) to Javanese Muslims. In contrast, modernist Islam does not regard tasawuf as a core teaching of Javanese Muslims, as explained by Mitsuo Nakamura. Nakamura conducted ethnographic research in Kotagede and used written sources from the Lebaran brochures produced by Muhammadiyah. Nakamura concludes that "Islamization" in Java will continue, as noted in his book "Bulan Sabit Terbit Di Atas Pohon Beringin," translated from "The Crescent Arises over the Banyan Tree: A Study of the Muhammadiyah Movement in a Central Javanese Town, c. 1910s-2010." The synthesis of Islam and Javanese culture will persist across time and space. Both Javanese Islam (Nusantara) by Woodward and modernist Islam by Nakamura, studied in these two books, represent a continuing process of intersection between Islam and local culture.Keywords: Javanese Islam, Traditional Islam, Modernist Islam, Muhammadiyah